The type of the land crab Cardisoma hirtipes Dana, 1851 (Crustacea: Brachyura: Gecarcinidae) - Ng, Peter K. L.; Clark, Paul F. (Zootaxa, 2014)
In describing a new species of land crab, Discoplax celeste, from Christmas Island, eastern Indian Ocean, Ng & Davie (2012: 95) selected a neotype for the related Discoplax hirtipes (Dana, 1851), originally described from Fiji as a species of Cardisoma Latreille, 1828. They commented that the type material was no longer extant and a neotype was necessary to stabilise the taxonomy of the species and its allies. The neotype they selected was a recently collected male specimen (64.2 × 53.0 mm, Zoological Reference Collection of the Raffles Museum of Biodiversity Research (now the Lee Kong Chian Natural History Museum), National University of Singapore, ZRC 2010.0415) from Fiji, with colour information as well as fresh tissues that could be used for genetic studies. Evans (1967: 410), however, had listed a syntype specimen of Cardisoma hirtipes in The Natural History Museum (NHM) (then the British Museum (Natural History), London)with the catalogue number 1861.44. The neotype selection of Ng & Davie (2012) thus appears to be unwarranted. Türkay (1974: 233), in revising the family, also listed among his material examined the following: “Südsee, Viti (1 Go/1 des Holotypus von Cardisoma hirtipes DANA 1851)”. No other data was provided, consequently it was unclear whether any specimen or only the gonopod was actually examined and where it was deposited. There was no other mention of this material in the text.